A bibliometric analysis of mental health among high school students - Song, Shilong; Yu, Wenbing; Li, Shuoqi; Sun, Wenze; Fu, Jiannan; Cheng, Qi (Frontiers in Psychiatry, 2024)
BackgroundIn recent years, with the increase in academic pressure and changes in social environment, especially after the outbreak of COVID-19, there has been a significant impact on the mental health of high school students. This trend, which is concerning, requires a systematic bibliometric analysis to develop effective preventive and remedial measures.ObjectiveThis study aims to identify and analysis the research hotspots, frontiers and emerging trends in the field of high school students’ mental health over the past two decades using CiteSpace software. These findings provide important insights that can shape future research agendas and guide targeted interventions to improve the mental health outcomes of this vulnerable group.MethodsThis study utilized the Web of Science Core Collection database as its data source to retrieve literature pertaining to high school students’ mental health from January 1, 2004, to January 1, 2023. The initial search yielded 1,764 relevant documents. After manually screening to exclude duplicates, conference proceedings, announcements, and irrelevant documents, a total of 1,748 relevant documents were retained. The research employed the CiteSpace 6.2.R4 tool to evaluate various bibliometric indicators of the included literature, including statistics on institutional and author publication volumes, as well as co-citation analysis.ResultsA total of 1,748 English-language documents were retrieved, showing an upward trend in publications on high school students’ mental health from 2004 to 2024. The research hotspots primarily focus on COVID-19 pandemic, depression, bullying, substance abuse, sexual behavior, Physical Education and their relationships with the mental health of high school students. Future research trends may focus on studies investigating the relationships between the use of electronic cigarettes, sleep disorders, internet addiction, and the mental health of high school students.ConclusionIn addition to the six major research hotspots of COVID-19 pandemic, Depression and stress, Suicidal ideation, Bullying, Sexual behavior and Physical education. Researches should pay more attention to the use of electronic cigarettes, sleep disorders, and Internet addiction among high school students.